Strategi Ketidaksantunan Berbahasa dalam Wacana Keagamaan - Hanifullah Syukri; Henry Yustanto; F.X. Sawardi; Miftah Nugroho; Chattri. S Widyastuti; Hesti Widyastuti; Bakdal Ginanjar (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
This study aims to describe the types of language impoliteness strategies in the discourse of religious texts, especially Islam. A pragmatic approach is used in this study. The data of this research are in the form of words, phrases, clauses, or sentences that contain impoliteness. The research data sources come from three discourses of Islamic religious texts taken from Youtube in 2020. The data collection method used is the download method. The research data were analyzed using contextual analysis methods. The results showed that there were four types of language impoliteness strategies found in three religious text discourses, namely (i) direct impoliteness strategies, (ii) positive impoliteness strategies, (iii) negative impoliteness strategies, and (iv) pseudo politeness strategies or sarcasm. The type of impoliteness strategy that is most commonly found in the discourse of religious speech texts is a negative impoliteness strategy with the most widely applied sub strategi is degrading sub strategi. The pseudo-politeness strategy or sarcasm is the least used strategy. The imbalance of power or social power between speech participants is the dominant factor in influencing the emergence of language impoliteness in the discourse of religious texts.